2023
DOI: 10.1371/journal.pone.0284962
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the two-pore domain potassium channel, THIK-1 and THIK-2, by G protein coupled receptors

Abstract: A member of THIK (two pore domain halothane-inhibited K+) channels, THIK-1, was reported as a target of Gi/o-coupled receptors (Gi/o-Rs) in neurons and microglia. We confirmed that in HEK293T cells the THIK-1 channel is activated by Gi/o-Rs and found that Gq-coupled receptors (Gq-Rs) also activates the channel. The effects of Gi/o-Rs and Gq-Rs were inhibited by the Gi/o inhibitor pertussis toxin and phospholipase C (PLC) inhibitor, respectively. The effects of Gi/o-Rs were attenuated when consensus Gβγ binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Second, activation of mGluRs in neocortex and hippocampus is known to modulate various K + channels [76][77][78][79][80][81] , although Ca 2+ and other channels can also be affected 82 . Third, signaling pathways from mGluRs to K2P channels have been identified using reduced expression systems 83,84 and in cerebellum granule cells 47,48,85 . K2P channels are responsible for leak and background currents, which are largely voltage-independent 86,87 .…”
Section: Stimulation Of Pom Afferents Modulates K2p Leak Channels Thr...mentioning
confidence: 99%
“…Second, activation of mGluRs in neocortex and hippocampus is known to modulate various K + channels [76][77][78][79][80][81] , although Ca 2+ and other channels can also be affected 82 . Third, signaling pathways from mGluRs to K2P channels have been identified using reduced expression systems 83,84 and in cerebellum granule cells 47,48,85 . K2P channels are responsible for leak and background currents, which are largely voltage-independent 86,87 .…”
Section: Stimulation Of Pom Afferents Modulates K2p Leak Channels Thr...mentioning
confidence: 99%
“…Recent studies have demonstrated that THIK-1 can be transiently activated by both G i/o and G q -coupled receptor pathways 16 , and can also be directly activated by anionic lipids such as PIP 2 and oleoyl-CoA 17 . In addition, THIK-1 exhibits direct inhibition by the phosphodiesterase inhibitor, 3-isobutyl-1-methyl-xanthine (IBMX) 18 as well as several small molecule inhibitors currently being developed as therapeutics 10,12 .…”
Section: Introductionmentioning
confidence: 99%